Long-Term Outcome and Prognostic Factors of Sporadic Colorectal Cancer in Young Patients: A Large Institutional-Based Retrospective Study. Issue 19 (May 2016) - Kim, Tae Jun; Kim, Eun Ran; Hong, Sung Noh; Chang, Dong Kyung; Kim, Young-Ho
Abstract : Abstract: The prognosis of early-onset sporadic colorectal cancer (CRC) patients remains controversial. The objective of this study was to assess the long-term outcome and prognostic factors of sporadic CRC in young patients. From 2006 to 2011, 8207 patients underwent curative or palliative surgery for CRCs in our institution. A total of 693 patients who were ⩽45 years old with sporadic CRC were enrolled as the young group. A total of 1823 patients aged between 56 and 65 years were identified as middle-aged control group for this study. Survival outcome and prognostic factors were compared between the two groups. Young patients had higher recurrence rate than older patients in stages I and II (8.8% vs 2.7%, P  <0.001). There was no significant difference of recurrence rate in stage III and IV cancers (27.5% vs 27.9%, P  = 0.325). Metachronous cancers were developed more frequently in young patients (1.4% vs 0.6%, P  = 0.038). Advanced stage CRC was diagnosed significantly more common in the young group (55.6% vs 47.9%, P  = 0.001). High microsatellite instability (MSI) tumors are less likely to have advanced stage cancers (odds ratio (OR) 0.23, 95% confidence interval (CI) = 0.07–0.70) or cancer recurrence (OR 0.11, 95% CI = 0.01–0.85) in young patients. Cancer-specific survival was worse in young patients than that in older patients (81.2% vs 87.8%, P  <0.001). However, there was no significant difference in cancer-specific survival for each stage between the two groups. Independent prognostic factors for survival in young patients were undifferentiated cancer (hazard ratio (HR) 2.30, 95% CI = 1.23–4.31) and 3 months or longer duration of symptom (HR 2.57, 95% CI = 1.34–4.94). Young women had better survival compared with young men (HR 0.55, 95% CI = 0.33–0.90). Prognosis of sporadic CRC in young patients is poorer than older patients, because of poorer histologic differentiation and delay in diagnosis. Early detection of CRC confers survival benefit to young patients. Because of higher recurrence rate and metachronous cancer risk, post-operative surveillance is also important in young patients. Abstract : Supplemental Digital Content is available in the text